EFL Learners’ Listening Strategy Awareness viewed from Their Learning Styles in the Extensive Listening Class - Dodi Mulyadi (E-Structural (English Studies on Translation, Culture, Literature, and Linguistics), 2018)
Abstract. Albeit listening comprehension as the vital role of language input, most EFL students have a somewhat negligent concern of it in the process of mastering EFL. Accordingly, the listening educators need to confirm students’ listening strategy awareness related to their learning styles for enhancing the quality of teaching listening. To this end, the study aims at assaying EFL students’ listening strategy awareness between visual, auditory, and kinesthetic learners who got an explicit strategy instruction of Extensive listening class and those who did not get the explicit strategy instruction.   The participants of the study were 38 sophomore EFL students of English departments at Universitas Muhammadiyah Semarang. Listening strategy awareness questionnaire, learning style questionnaire, and interview were utilized as the data collection instruments. The results elucidated that explicit listening strategy instructions have raised students’ direct attention strategies. Strategies of interpreting the meaning in their head and translating keywords that they have listened potentially impact on students’ mental translation strategy awareness. Indeed, visual learners in the control group have a higher strategy awareness dealing with person knowledge than in an experimental group. Then, auditory learners have similar scores for both groups — meanwhile, a bit higher score of person knowledge possessed by the kinesthetic learners in the experimental group. However, the statistical findings elucidate that there are no significant differences between the experimental and control group. Interview results confim that explicit strategy instruction of extensive listening class enables learners to create a good atmosphere in listening class, and their competence of listening instruction.